Performance audit as one of the most important methods of state budget control - Nazmiden, B.T.; Kabiev А.А.; Rakhimova, G.A.; Esenova, G.Sh. (BUKETOV BUSINESS REVIEW, 2019)
As world practice shows that the system of financial control and state audit, which in our country was introduced seemingly recently, in each country has its own characteristics. In Kazakhstan, financial control and state audit is an integral part of public administration and a tool for monitoring the efficiency of management and the use of budgetary funds, including an audit of financial statements, compliance audit and performance audit. In this article, the authors reveal the issues of efficiency audit in the structure of state audit as the most important method of conducting state budgetary control. The relevance of the topic is related to the fact that in our country such problems as budget planning and budget execution are still in the spotlight. In this regard, the importance of the bodies of financial control and state audit, functions of which include ensuring the financial discipline of recipients of budget money, is growing. In the article, the authors analyzed the reporting data of the bodies of financial control and state audit, which showed that the amount of funds returned and recovered to the budget tends to increase. However, there are still problems that need attention. According to the authors, it is necessary to strengthen the work on the methodological support and training of personnel of the state audit.